2013
DOI: 10.1371/journal.ppat.1003655
|View full text |Cite
|
Sign up to set email alerts
|

The Suf Iron-Sulfur Cluster Synthesis Pathway Is Required for Apicoplast Maintenance in Malaria Parasites

Abstract: The apicoplast organelle of the malaria parasite Plasmodium falciparum contains metabolic pathways critical for liver-stage and blood-stage development. During the blood stages, parasites lacking an apicoplast can grow in the presence of isopentenyl pyrophosphate (IPP), demonstrating that isoprenoids are the only metabolites produced in the apicoplast which are needed outside of the organelle. Two of the isoprenoid biosynthesis enzymes are predicted to rely on iron-sulfur (FeS) cluster cofactors, however, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
173
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(183 citation statements)
references
References 72 publications
8
173
2
Order By: Relevance
“…The antimalarial effect of inhibition of Fe-S assembly on target proteins in the apicoplast has been recently demonstrated through the generation of dominant negative SufC mutant parasites (7). These parasites lost the apicoplast and the organellar genome and were viable only when supplemented with isopentenyl pyrophosphate, an essential product of the apicoplast DOXP pathway that supports parasite survival in blood culture even when the apicoplast is lost (46).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The antimalarial effect of inhibition of Fe-S assembly on target proteins in the apicoplast has been recently demonstrated through the generation of dominant negative SufC mutant parasites (7). These parasites lost the apicoplast and the organellar genome and were viable only when supplemented with isopentenyl pyrophosphate, an essential product of the apicoplast DOXP pathway that supports parasite survival in blood culture even when the apicoplast is lost (46).…”
Section: Resultsmentioning
confidence: 99%
“…It harbors unique pathways such as the type II fatty acid biosynthesis pathway, the DOXP pathway of isoprenoid synthesis, and the heme biosynthesis pathway (3)(4)(5), that offer potential novel sites for drug intervention at different stages of the infection cycle. In addition, experimental evidence of the existence of the sulfur mobilization (SUF) pathway for biogenesis of Fe-S clusters on organellar proteins was provided by our laboratory (6), and this pathway has recently been shown to be essential for apicoplast maintenance in erythrocytic stages of Plasmodium falciparum (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Structural and mechanistic understanding of Suf systems may enable the development of new antibiotics that target the SufBCD complex. Indeed, a recent study demonstrated that the Suf system of malaria parasites is essential for survival and plays a fundamental role in maintaining the apicoplast organelle (58). In eukaryotes, including mammalian cells, the ISC system (59) and its dependent CIA system (60) are responsible for nascent Fe-S cluster biogenesis.…”
Section: Discussionmentioning
confidence: 99%